Case report: Remedial surgical treatment of aorto-duodenal fistula with infected aneurysm after endovascular aortic repair - Li, Wen-Dong; Wu, Guang-Yan; Song, Bin; Zhao, Jie; Li, Xiao-Qiang; Zhou, Min (Frontiers in Cardiovascular Medicine, 2022)
Aorto-duodenal fistula (ADF) is a rare cause of upper gastrointestinal bleeding, but it is associated with high mortality. It usually occurs in patients with prior aortic surgery or who have undergone aortic graft placement. Abdominal aortic aneurysm (AAA) might be a cause of primary ADF, which could develop into sudden shock. Because ADF is difficult to diagnose, surgery to correct it has a poor outcome. We here report the successful treatment of an ADF complicated with infected AAA after endovascular repair of a ruptured aneurysm of the iliac artery.